PUBLIC AFFAIRS PROGRESS REPORT DECEMBER 1987 - SPARBER P; ROSS J; STUNTZ S; FOLEY C; RANSOME, SHARON; PANZER, FRED; MORAN, BRENNAN; OSBORNE, LISA; DEDICK, ANNE; LYONS, JOHN (Tufts Archival Research Center, 2007)
Confidential; Public Affairs Management Report for 1987 detailing responsibilities for various issues. Includes issues such as excise tax, public smoking issues, advertising, accidental fires and media relations.